Can micro-insurance cover natural risks? - Esther Gehrke (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Natural hazards affect human well-being in several ways. They destroy livelihoods, cause huge losses in production, reduce income and damage property. Many poor people in developing countries are especially vulnerable to natural risks, not only because they depend on agricultural production as their major source of income, but also because they are often obliged to settle in risk-prone areas such as hillsides, river basins, etc. It has become even more important to find adequate means to manage natural risks because climate change is causing many of them to increase in frequency and degree. Micro-insurance for natural risks has been proposed as a helpful tool to improve poor peoples' risk management, and several development-cooperation projects have been initiated in order to promote micro-insurance for natural risks. However, it is not yet clear which risks are insurable in micro-insurance and which are not. This paper therefore analyses which natural risks could be covered by micro-insurance and shows how this can be done.
Keywords: 330